Distinctive Roles for α7*- and α9*-Nicotinic Acetylcholine Receptors in Inflammatory and Autoimmune Responses in the Murine Experimental Autoimmune Encephalomyelitis Model of Multiple Sclerosis - Liu, Qiang; Whiteaker, Paul; Morley, Barbara J.; Shi, Fu-Dong; Lukas, Ronald J. (Frontiers in Cellular Neuroscience, 2017)
Previous studies have demonstrated immunosuppressive and anti-inflammatory effects of nicotine, including in the experimental autoimmune encephalomyelitis (EAE) model in mice of some forms of multiple sclerosis. Other studies using knock-out mice have implicated nicotinic acetylcholine receptors containing α7, α9, or β2 subunits (α7*-, α9*- or β2*-nAChR) in different, disease-exacerbating or disease-ameliorating processes. These outcomes are in harmony with gene expression analyses showing nAChR subunit mRNA in many classes of immune system cell types. Consistent with influences on disease status, predictable effects of nAChR subunit (and subtype) knock-out, or of nicotine exposure, are seen on immune cell numbers and distribution and on cytokine levels or other markers of immunity, inflammation, demyelination, and axonal degradation. Providing support for our hypotheses about distinctive roles for nAChR subtypes in EAE, here we have used direct and adoptive EAE induction and a nAChR subunit gene double KO (DKO) strategy. Immune cell expression of nAChR α9 subunits as protein is demonstrated by immunostaining of isolated CD4+, CD8+, CD11b+ and CD11c+ cells from wild-type mice, but not in cells from nAChR α9 subunit knock-out animals. Nicotine exposure is protective against directly-induced EAE in wild-type or α7/α9 DKO animals relative to effects seen in wild-type/vehicle-treated mice, but, remarkably, EAE is exacerbated in vehicle-treated α7/α9 DKO mice. Brain lesion volume and intra-cranial inflammatory activity similarly are higher in DKO/vehicle than in wild-type/vehicle-treated animals, although nicotine’s protective effects are seen in each instance. By contrast, in adoptive transfer studies, disease severity is attenuated and disease onset is delayed in recipients of splenocytes from wild-type animals treated with nicotine rather than with vehicle. Moreover, protection as seen in nicotine-treated wild-type animals is the same in recipients of splenocytes from nAChR α7/α9 DKO mice irrespective of their exposure to nicotine or vehicle. When combined with previous observations, these findings are consistent with disease exacerbation (or even induction) being mediated at least in part via α9*-nAChR in peripheral immune cells. They also suggest protective roles of central nervous system α7*-nAChR. The results suggest that both α7*- and α9*-nAChR are potential targets of therapeutic ligands to modulate inflammation and autoimmunity.